Water vapor in Titan's stratosphere from Cassini CIRS far-infrared spectra - Cottini, V; Nixon, C; Jennings, D; Anderson, C; Gorius, N; Bjoraker, G; Coustenis, A; Teanby, N; Achterberg, R; Bezard, B; de Kok, R; Lellouch, E; et al. (2012)
Here we report the measurement of water vapor in Titan's stratosphere using the Cassini Composite Infrared Spectrometer (CIRS, Flasar, F.M. et al. [2004]. Space Sci. Rev. 115, 169-297). CIRS senses water emissions in the far infrared spectral region near 50μm, which we have modeled using two independent radiative transfer codes (NEMESIS (Irwin, P.G.J. et al. [2008]. J. Quant. Spectrosc. Radiat. Trans. 109, 1136-1150) and ART (Coustenis, A. et al. [2007]. Icarus 189, 35-62; Coustenis, A. et al. [2010]. Icarus 207, 461-476). From the analysis of nadir spectra we have derived a mixing ratio of 0.14±0.05ppb at an altitude of 97km, which corresponds to an integrated (from 0 to 600km) surface normalized column abundance of 3.7±1.3×10 14molecules/cm 2. In the latitude range 80°S to 30°N we see no evidence for latitudinal variations in these abundances within the error bars. Using limb observations, we obtained mixing ratios of 0.13±0.04ppb at an altitude of 115km and 0.45±0.15ppb at an altitude of 230km, confirming that the water abundance has a positive vertical gradient as predicted by photochemical models (e.g. Lara, L.M., Lellouch, F., Lopez-Moreno, J.J., Rodrigo, R. [1996]. J. Geophys. Res. 101(23), 261; Wilson, E.H., Atreya, S.K. [2004]. J. Geophys. Res. 109, E6; Hörst, S.M., Vuitton, V., Yelle, R.V. [2008]. J. Geophys. Res., 113, E10). We have also fitted our data using scaling factors of ~0.1-0.6 to these photochemical model profiles, indicating that the models over-predict the water abundance in Titan's lower stratosphere. © 2012 Elsevier Inc..